2011
DOI: 10.4236/ajac.2011.23047
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Determination of Benzophenone-3 in Sunscreen Preparations Using Boron-Doped Diamond Electrodes

Abstract: AbstracA new electroanalytical procedure was developed for the determination of Benzophenone-3 (BENZO) in commercial sunscreen as the active ingredient. The procedure is based on the use of electrochemical methods as cyclic and square-wave voltammetry, with boron-doped diamond (BDD) electrodes. The reduction of BENZO in Britton-Robinson buffer (0.1 mol·L -1 ) using this type of electrode gives rise to one irreversible peak in -1.30 V (versus Ag/AgCl) in presence of cationic surfactant cetyltrimethylammonium br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Our research group has demonstrated that electroanalytical techniques can be effectively used to develop alternative methods, by using these techniques it was possible to quantify several active sunblocking agents after analyzing different cosmetic samples [14][15][16][17][18]. Accordingly, in one of our developed methods [14], differential-pulse polarography and a mercury-dropping electrode were used to determine 2-ethylhexyl-4-methoxycinnamate (EHMC), individually and in the presence of 2-hydroxy-4-methoxybenzophenone (BENZO-3) or 4-methylbenzylidene camphor (4-MBC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has demonstrated that electroanalytical techniques can be effectively used to develop alternative methods, by using these techniques it was possible to quantify several active sunblocking agents after analyzing different cosmetic samples [14][15][16][17][18]. Accordingly, in one of our developed methods [14], differential-pulse polarography and a mercury-dropping electrode were used to determine 2-ethylhexyl-4-methoxycinnamate (EHMC), individually and in the presence of 2-hydroxy-4-methoxybenzophenone (BENZO-3) or 4-methylbenzylidene camphor (4-MBC).…”
Section: Introductionmentioning
confidence: 99%
“…On the proposed methods, 4-MBC [15] as well as 4-MBC, BENZO-3, and OMC [16] were determined at trace levels in commercial sunscreen products via a simple and fast pre-treatment protocol. In another work, a method employing cyclic and square wave voltammetry was used to study the voltammetric behavior and to determine BENZO-3 onto a boron-doped diamond (BDD) electrode [17]. The methodology was applied to the analysis of commercial preparations and determination of BENZO-3, as the active ingredient, at concentration levels of 1.0×10 −5 mol L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies are essential to ensure that the product is stable throughout its designated shelf life. The stability was carried out for thirty days at temperatures 40 ± 2°C and relative humidity at 75 ± 5% using stability chamber 12,13,14 .…”
Section: Stability Studies As Per Ich Guidelinesmentioning
confidence: 99%